Mathematical Models and Algorithmization of Monitoring Control an Affiliated Network in Maintenance Service Distributed Organizations - Kravets, Oleg Jakovlevich; Choporov, Oleg Nikolaevich; Bolnokin, Vitaly Evgenievitch (Calitatea, 2018)
The paper considers some problems and peculiarities of modeling and efficient development in social and economic monitoring. As we know, accurate and enhanced monitoring of the market and customer data base is a necessary requirement for the organization's survival in intense competition. The research subject is a maintenance service distributed organization possessing a network of affiliates and representatives. Improving monitoring processes will ensure timely revealing potential situations of customers' change of a service company, broadening the customer data base and eventual strengthening the company's position in competition. The authors have used the methodology of conceptual and mathematical modeling based on monitoring intensity. The paper presents the analysis and heuristic approach towards rationalized management of monitoring researches, proposes modeling and algorithmization of managing customers' changing maintenance service distributed organization affiliates (representatives) and adaptive techniques of monitoring management under organizational and economic restrictions. Streamlining monitoring study enables to optimize the monitoring of clients, especially those expected to be ready to change the service organization. In our view, the obtained results are to be applied both in static and dynamic configuration of distributed companies. The article gives heuristic methods of planning monitoring researches in organizational and economic systems, featuring the accounting of restrictions to the total monitoring amount and providing short- and long-term monitoring planning in the course of data collection needed for management decisions to enhance the organization competitiveness.